Neurocisticercose: incidência, diagnóstico e formas clínicas - Horácio M. Canelas (Arquivos de Neuro-Psiquiatria)
Cysticercosis of the nervous system is a tribute paid to underdevelopment. The tables of incidence show that although it is practically unknown in some countries, it represents a curse to the less fortunate habitants of Asia, Africa and Latin America. The Latin American countries pay a heavy toll; known statistics show a ponderous incidence in Mexico, Chile, Peru and Brasil. The statistics referring to the States of São Paulo and Rio de Janeiro, Brasil, where a rather thorough study of the problem has been made through the past years, portray the seriousness of the problem. Autopsy studies show an incidence of 0.12 to 1.10 percent in general hospitals, and of 0.40 to 3.60 percent in neuropsychiatric hospitals. In the Department of Neurology of the University of São Paulo School of Medicine, the incidence ranged from 2.90 to 3.39 percent in ward patients, and from 0.31 to 0.55 percent in out-patients. This Department had 41,328 patients from 2-14-1945 to 8-31-1961, of which 4,900 were ward patients. A total of 276 cases of neurocysticercosis was observed. A correlation between the incidence of neurocysticercosis and hygienic-social conditions is made evident by the fact that only one fourth of our patients came from large cities, while the remaining came from the hinterland, where living conditions are notedly worse. The differences in incidence regarding to sex and race were only apparent. Regarding to age incidence, 54 cases were younger than 10 years, and about half of the cases were in the 21 to 40 age group. The youngest patient was 14 months, the oldest 69 years old. The diagnosis of neurocysticercosis was based on at least one of the following data: a) recovery of the parasite during surgery and/or autopsy; b) positive complement fixation test (CFT) for cysticercosis in the cerebrospinal fluid, with or without increase in eosinophiles; c) positive CFT for cysticercosis in the blood associated to X-ray demonstration of intracranial parvinodular calcifications. The CFT for cysticercosis in the cerebrospinal fluid, performed in 271 patients, was positive in 240 (88.6 percent). The same test in the blood was positive in 70.2 percent of the cases. The correlation between these data was not significant. Intracranial mottling calcifications were found in only 19.2 percent of the cases. Therefore, in 240 cases the diagnosis was based on cerebrospinal fluid findings, confirmed by surgery and/or autopsy in 58 patients. In 13 cases, despite a normal cerebrospinal fluid, the diagnosis was made by a positive CFT for cysticercosis in the blood, associated to the finding of intracranial parvinodular calcifications. In the remaining 23 cases the parasite was recovered during surgery and/or autopsy. Regarding to its clinical features, the disease was manifested under three separate forms: acute (meningoencephalitis, cerebral edema, ventricular obstruction, ischemic softening secondary to endarteritis), subacute and chronic (specially the purely convulsive clinical pictures). The symptoms had been present for less than 1 month in 40 cases, from 1 to 12 months in 116 cases, and for more than 1 year in 115 cases; in 5 cases this information was not ascertained. Our cases were classified, regarding to the clinical symptomatology, in hypertensive, convulsive, with focal or diffuse neurologic manifestations, and psychic. These forms were found as single manifestations in the following rates: 46.6 percent of the convulsive, 35.9 percent of the hypertensive, 24.5 percent of the cases with focal or diffuse neurologic symptoms, and none of the psychic. There was association of intracranial hypertension and convulsive seizures in 69 cases (25.0 percent). In 26 cases (9.4 percent) there were, in addition, psychic symptoms. In 24 cases (8.7%) focal or diffuse neurologic manifestations were associated to intracranial hypertension and convulsions. In general, the hypertensive forms were more common than the convulsive forms. Hypertensive cases prevailed in the Emergency Service (85.1 percent of cases), while in the Out-patient Department the convulsive forms were more frequent (87.8 percent). In 85 hypertensive cases the site of cerebrospinal fluid block was investigated either by X-ray, surgery or autopsy, and was determined to be ventricular in 23 cases, and cisternal in 46 cases. Racemous cysticerci more often cause obstructive forms. Seizures were present in 148 patients (53.6 percent), 79 of which having not intracranial hypertension. The incidence of generalized and focal seizures was approximately the same. Psychomotor epilepsy was clinically diagnosed in 5 cases, 2 of which presented temporal foci in the EEG examination. The electroencephalograms of 148 cases were analyzed regarding to topography of findings and clinical manifestations. Diffuse alterations and bilateral occipital foci were more common with intracranial hypertension, while isolated foci were more frequent with purely convulsive cases. Normal readings were also common with the latter (44.0 percent). Focal or diffuse neurologic manifestations were associated to intracranial hypertension and/or convulsions in 74 patients (26.8 percent), but were found as single symptomatology in only 24 patients (8.7 percent). In this group ataxia was the main finding, being cerebellar (33 cases) or mixed (3 cases). Central paralytic forms (monoplegia, hemiplegia and tetraplegia) were observed in 24 cases, sometimes starting as a vascular ictus. Cranial nerve involvement was noted in 12 patients, usually as a cerebello-pontine syndrome. Spinal cord manifestations characterized 8 cases. Paralysis of vertical gaze was observed in 5 instances. Extrapyramidal forms were rare (4 cases), as well as neuralgias of the trigeminal or glossopharyngeal nerves (3 cases) and infundibulo-hypophyseal syndromes (2 cases). Difuse cerebrospinal symptomatology was observed in 2 cases. Psychic disturbances were evident in 63 patients (22.8 percent), usually associated to intracranial hypertension, isolated (25 cases) or joined to seizures (26 cases). The mortality rate was 25.9 percent. Of 63 operated patients, 28 died. The results of various schemes of drug therapy cannot be well evaluated, due to the possibility of spontaneous remission, and to difficulties of prolonged follow-up. In view of the poor surgical results, and debatable effects of medical treatment, emphasis should be given to prophylactic measures, through campaigns of Public Health.